Pilgrimages to the Shrine of Fatima: Considerations about the ritualistic dimension of religiosity - Mónico, Lisete S. Mendes (2018)
Looking to understand religiosity as a social factor, contributory of constructions of meaning and omnipresent in diverse historical and cultural universes, this article focuses on the ritualistic dimension of religiosity. Adopting as a research problem the religious pilgrimages, take particular note of the shrines as symbolic markers towards the supernatural. This work has a double aim: to carry out a review and critical analysis of the religious pilgrimages and to study the specificity of the pilgrimages to the Shrine of Fatima, located in Portugal. After a brief mention of the dialectic dissidence-coexistence of ancient religious practices in secularized societies, the concepts of worship, rites and sacrifices are revisited. There follows a more in-depth analysis of the theme of pilgrimages to shrines, from the concept and historical review to the particularity of pilgrimages to the Shrine of Fatima, the latter viewed as a geo-symbol of religious tourism in Portugal. The results of a survey of 784 pilgrims to the Shrine of Fátima are presented, focusing on the beliefs, experiences, perceptions, purposes and expectations regarding the pilgrimage, as well as the nature of the requests addressed to the Lady of Fatima and promises fulfilled. Throughout the article the pilgrim character is emphasized, not neglecting the analysis of the active, voluntary and sacrificial behavioral implication as legitimating the benefits already granted or to be granted.